DAMPAK RENOVASI TAMAN WISATA LOANG BALOQ TERHADAP PENYERAPAN TENAGA KERJA DAN PENDAPATAN MASYARAKAT YANG BERAKTIVITAS EKONOMI DI TAMAN WISATA LOANG BALOQ - Fadhlillah, Bagus Rizqy; Daeng, Akung; Wahidin, Wahidin (Laboratorium Riset Ekonomi, 2025)
This study aims to analyze the impact of the Loang Baloq Tourism Park Renovation on the Absorption of Economic Welfare in Loang Baloq Tourism Park. The type of data used in this study is primary data. The population in this study is all employees and traders in Loang Baloq Tourism Park. The data analysis procedure in this study includes a paired t test which was previously carried out to test the normality of the results of the study with the title